Study failure at Czech universities in an international context - Prokop, Jiří (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The paper focuses on the issue of academic failure of university students. First, the concept of academic failure and other related terms are defined. Next, three perspectives are explained through which one can look at study failure. Much space is devoted to the analysis of foreign, European and Czech research, publications and professional studies in this field. We shall point out the factors that are most involved in school dropout.